Conserved and Diversified Gene Families of Monovalent Cation/H+ Antiporters from Algae to Flowering Plants - Chanroj, Salil; Wang, Guoying; Venema, Kees; Zhang, Muren W.; Delwiche, Charles F.; Sze, Heven (Frontiers in Plant Science, 2012)
All organisms have evolved strategies to regulate ion and pH homeostasis in response to developmental and environmental cues. One strategy is mediated by cation-proton antiporters (CPA). CPA1 genes found in bacteria, fungi, metazoa and plants have been functionally-characterized; though roles of plant CPA2 genes in KEA (K+-efflux antiporter) and CHX (cation/H+ exchanger) families are largely unknown. Phylogenetic analysis showed that three clades of the Na+-H+ exchanger (NHX) family have been conserved from single-celled alga to Arabidopsis. These are i) plasma membrane-bound SOS1/AtNHX7 that share ancestry with prokaryote NhaP, ii) endosomal AtNHX5/6 that is part of the eukaryote Intracellular-NHE clade, and iii) a vacuolar NHX clade (AtNHX1-4) specific to plants. Early diversification of KEA genes possibly from ancestral genes of a cyanobacterium is suggested for three K+-efflux antiporter clades (KEA/Kef) seen in all plants. Intriguingly, the CHX gene family blossomed from a few members in early land plants to >40 genes in legumes. Homologs from spirogyra or moss share high similarity with guard cell-specific AtCHX20, suggesting that AtCHX20 and its relatives (AtCHX16-19) are founders of the family. Evolutionary analysis suggests pollen-expressed CHX genes appeared later in monocots and early eudicots. AtCHX proteins have been localized to intracellular and plasma membrane of plants, and shown to mediate K+ transport and pH homeostasis. Thus KEA genes are conserved from green algae to angiosperms, and their presence in red algae and secondary endosymbionts suggest a role in plastids. In contrast, AtNHX1-4 subtype evolved in ancestral plants to handle ion homeostasis of vacuoles in all cell types. The strong presence of CHX genes in land plants, but not in metazoa or fungi, would infer a role of ion and pH homeostasis at dynamic endomembranes to support vegetative and reproductive success of flowering plants.